Multiplex PCR and Sequence Analysis to Investigate Genetic Diversity of Fasciola Isolates from Cattle and Sheep in Turkey - Uzun, Veysel; Celik, Figen; Simsek, Sami; Kesik, Harun Kaya; Kilinc, Seyma Gunyakti; Zhang, Xiaocheng; Cao, Jianping (Mdpi, 2022)
Fasciolosis is a highly prevalent helminthic infection caused by Fasciola hepatica and F. gigantica. With the aim of identifying hybrid Fasciola flukes, multiplex PCR was performed to amplify the pepck gene. Furthermore, to determine Fasciola haplotypes, mitochondrial nad1 gene was amplified and sequenced, and phylogenetic analyses were performed. Adult Fasciola isolates were collected from 51 cattle and 51 sheep, genomic DNA was isolated, and one-step multiplex PCR was subsequently performed to amplify pepck. Isolates that generated a 510 bp band were identified as F. gigantica, those that generated a 241 bp band were identified as F. hepatica, and those that generated both bands were identified as hybrid (aspermic) flukes. Multiplex PCR data identified four isolates as F. gigantica and 84 as F. hepatica. Fourteen hybrid isolates (five cattle and nine sheep) were identified. On unidirectional DNA sequence analysis of nad1 PCR products, three sequences were identified as F. gigantica and 99 as F. hepatica. In addition, only 4 of 87 haplotypes detected for F. hepatica nadl sequences were found to be previously reported, while the remaining 83 are unique to this study. To summarize, this study is the first to report the existence of hybrid Fasciola flukes and 83 unique haplotypes of F. hepatica in Turkey.
Keywords: Fasciola hepatica; F. gigantica; nad1; haplotype; multiplex PCR; hybridization; introgression